Healthcare experiences of patients with chronic heart failure in Germany: a scoping review. Issue 10 (10th October 2020) - Dieckelmann, Mirjam; Petersen, Juliana J; Güthlin, Corina; Reinhardt, Felix; Plath, Jasper; Jeitler, Klaus; Semlitsch, Thomas; Gerlach, Ferdinand M; Siebenhofer, Andrea
Abstract : Objectives: To review systematically the past 10 years of research activity into the healthcare experiences (HCX) of patients with chronic heart failure (CHF) in Germany, in order to identify research foci and gaps and make recommendations for future research. Design: In this scoping review, six databases and grey literature sources were systematically searched for articles reporting HCX of patients with CHF in Germany that were published between 2008 and 2018. Extracted results were summarised using quantitative and qualitative descriptive analysis. Results: Of the 18 studies (100%) that met the inclusion criteria, most were observational studies (60%) that evaluated findings quantitatively (60%). HCX were often concerned with patient information, global satisfaction as well as relationships and communication between patients and providers and generally covered ambulatory care, hospital care and rehabilitation services. Overall, the considerable heterogeneity of the included studies' outcomes only permitted relatively trivial levels of synthesis. Conclusion: In Germany, research on HCX of patients with CHF is characterised by missing, inadequate and insufficient information. Future research would benefit from qualitative analyses, evidence syntheses, longitudinal analyses that investigate HCX throughout the disease trajectory, and better reporting of sociodemographic data. Furthermore, research should include studies that are based on digital data, reports of experiences gained in under-investigated yet patient-relevant healthcare settings and include more female subjects.